The Internalization of Islamic Wasathiyah Values Within the Framework of Social Harmony - Sutrisna, Sutrisna (Millati: Journal of Islamic Studies and Humanities, 2025)
This article aims to provide solutions to the negative impacts on society in the era of Society 5.0 through the internalization of Islamic wasathiyah values within the social system. It uses a qualitative method with a phenomenological approach, employing the natural environment as the primary data source and humans as the main instrument. The analysis is conducted inductively. Data collection techniques include observation, documentation, focus group discussions, and interviews. Data analysis is carried out through reduction, categorization, display, and conclusion. The process of internalizing Islamic wasathiyah values, social norms, ethics, legal obedience, and discipline in social life involves making appropriate decisions in applying Islamic wasathiyah values such as tawassuth (moderation), i’tidal (balance), tasamuh (tolerance), syura (consultation), islah (reconciliation), and qudwah (role model), all aimed at the dignity of humanity. The social system functions as an organized network of relationships that forms a coherent whole or harmony between individuals, groups, and societal institutions, ultimately leading to social harmony. The embodiment of Islamic wasathiyah values in attitudes and behaviors through the social system, shared life with social norms and ethics, legal obedience, and discipline in community life, serves to create social harmony by integrating technology into life in a smart, humane, and sustainable manner. This fosters the development of a high regard for human dignity in daily activities, based on religion, morality, and ethics, while promoting cooperation, social sensitivity, and concern for the community and the environment.